Association of Clinical Presentation & Comorbidity Among Covid-19 Patients Admitted in Tertiary Care Hospital (Medical Forum Monthly, 2020)
Objective: To study the association of clinical features & comorbidity among Covid-19 patients admitted in tertiary care hospital.Study Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at the ABWA hospital and research center attached with Abwa Medical College, Faisalabad for the period of four months from April to July, 2020.Materials and Methods: Total 142 admitted Covid-19 patients were selected as participants to assess the range of symptoms experienced during active phase of infection.Results: Out of total 142 participants, 87.3 %( n=124) complaint of shortness of breath, 57.7%(n=82) had fever & 43.3% (n=62) had cough,27.5%(n=39) reported of body aches as compared to 14.1% (n=20) who had loose motions & 3.5%(n=5) who experienced irritability. Regarding comorbidity,49.3%(n=70) patients had Diabetes Mellitus,33.1%(n=47) Hypertension, 10.6%(n=15) Ischemic heart disease & 2.8%(n=4) had Chronic kidney disease.Conclusion: During the pandemic of corona infection, majority of the symptomatic patients admitted in hospital had pre-existing health issues i.e. Diabetes, Hypertension, Renal diseases & respiratory involvement. Moreover, the concurrence of Covid-19 infection with medical syndrome serve as a vital prognosis factor linked with complications with multi organ involvement, unexpected outcome & longer hospital stay. This implies that health care emergency services should be formulated and implemented in a way where supervised intensive care should be provided to the most vulnerable group. Moreover, extensive awareness campaigns should be carried out to identify the group at risk of mortality.